2021
DOI: 10.1177/23259671211035384
|View full text |Cite
|
Sign up to set email alerts
|

Prior Bone Marrow Stimulation Surgery Influences Outcomes After Cell-Based Cartilage Restoration: A Systematic Review and Meta-analysis

Abstract: Background: Cell-based cartilage restoration with autologous chondrocyte implantation (ACI) is a safe and effective treatment for symptomatic cartilage lesions. Many patients undergoing ACI have a history of prior surgery, including bone marrow stimulation (BMS). There is mounting evidence that a history of prior BMS may impede healing of the ACI graft. Purpose/Hypothesis: The purpose of this study was to compare the failure rates of primary ACI with ACI after prior BMS. We hypothesized that ACI after BMS woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(174 reference statements)
0
7
0
Order By: Relevance
“…It is cost-effective and not technically demanding, with an extremely low rate of patient morbidity. Moreover, it does not compromise the possibility of further additional surgeries [ 21 , 22 ] though a recent systematic review by Cogan et al demonstrated a higher failure rate for patients treated with autologous chondrocytes implantation (ACI) after a prior bone marrow stimulation technique (like microfracture) [ 23 ]. Moreover many studies demonstrated that the quality of cartilage repair tissue and the clinical outcomes are significantly better for patients with smaller chondral lesions [ 24 26 ]; therefore, the bigger chondral lesions should be addressed by recurring to more aggressive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It is cost-effective and not technically demanding, with an extremely low rate of patient morbidity. Moreover, it does not compromise the possibility of further additional surgeries [ 21 , 22 ] though a recent systematic review by Cogan et al demonstrated a higher failure rate for patients treated with autologous chondrocytes implantation (ACI) after a prior bone marrow stimulation technique (like microfracture) [ 23 ]. Moreover many studies demonstrated that the quality of cartilage repair tissue and the clinical outcomes are significantly better for patients with smaller chondral lesions [ 24 26 ]; therefore, the bigger chondral lesions should be addressed by recurring to more aggressive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…24 In contrast, autologous chondrocyte implant, although appropriate for larger defect areas, has worse outcomes after prior marrow stimulation and is not well-suited for deeper osteochondral defects or for those with subchondral change. 5 Osteochondral allograft transplant is a facile solution to treat deep and large osteochondral lesions, typically at least 2 cm 2 in surface area. By fitting an allograft osteochondral plug in a congruent fashion to the patient's articular surface, osteochondral allograft transplant provides a viable option for defects with extensive subchondral edema, even in the setting of prior marrow stimulation, without donor site morbidity.…”
mentioning
confidence: 99%
“… 24 In contrast, autologous chondrocyte implant, although appropriate for larger defect areas, has worse outcomes after prior marrow stimulation and is not well-suited for deeper osteochondral defects or for those with subchondral change. 5 …”
mentioning
confidence: 99%
“…When performing the bone marrow stimulation procedure, it is important to note that the structural and functional architecture of the subchondral bone is of the utmost importance and can play a vital role in the long-term outcome of the index bone marrow stimulation procedure, as well as on any subsequent cartilage procedure that may follow. 13 , 14 Although previous literature has shown good short-term outcomes in appropriately selected patients, recent literature has suggested that the outcomes of bone marrow stimulation may worsen after 5 years, primarily because of the poor quality of the fibrocartilage replacement tissue that is formed. 7 , 15 The size of the instrument, depth of penetration into the subchondral bone, and resulting trabecular compaction around the channel have been implicated in this fibrocartilage tissue, because it may affect the ability of the technique to cause regeneration versus degeneration.…”
mentioning
confidence: 99%